Learning Motivation in Islamic Religious Education (IRE) Viewed from Cognitive Strategies: A Study of Grade XI Students at SMAN 1 Bagan Sinembah - Siti Eka Eriyani (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to analyze the effect of cognitive aspect strategies on student learning motivation in Islamic Religious Education (PAI) subjects at SMAN 1 Bagan Sinembah, Rokan Hilir Regency, Riau. This type of research is quantitative with data collection techniques through closed questionnaires distributed to 51 Muslim class XI students. The sampling technique used purposive sampling, while data analysis was conducted using SPSS software. The results of the analysis show that cognitive strategies have a significant effect on student learning motivation. The findings reveal that learning motivation is shaped by students' internal strengths as well as the teacher's role in creating interactive, reflective and contextualized learning. Cognitive strategies encourage students to connect teaching materials with their experiences, thus increasing learning engagement and motivation.